Fostering EFL learners’ motivation, anxiety, and self-efficacy through computer-assisted language learning- and mobile-assisted language learning-based instructions - Dong, Li; Jamal Mohammed, Shireen; Ahmed Abdel-Al Ibrahim, Khaled; Rezai, Afsheen (Frontiers in Psychology, 2022)
In the literature, a mass of studies has inspected the effects of Computer-Assisted Language Learning (CALL), Mobile-Assisted Language Learning (MALL) on Iranian EFL learners’ achievement. However, their effects of CALL and MALL on psychological factors, such as motivation, foreign language anxiety, and self-efficacy have largely remained unexplored. Thus, this study explored the effects of CALL and MALL, and Face-to-Face (FTF) learning environments on Iranian EFL learners’ motivation, anxiety, and self-efficacy. To this aim, using a random sampling method, a total of 137 male EFL intermediate learners were selected. They were homogenized using the Oxford Quick Placement test (OQPT). Based on their test scores, a total of 90 EFL learners were selected and randomly assigned to three groups, namely CALL (n=30), MALL (n=30), FTF (n=30). Then, the participants’ motivation, anxiety, and self-efficacy were gauged prior to the instructions. Afterward, they received instruction lasting 25 sessions holding twice a week. At the end of the instruction, the participants’ motivation, anxiety, and self-efficacy were measured. The collected data were analyzed through a one-way MANOVA. Findings evidenced that the experimental groups’ motivation, anxiety, and self-efficacy were positively affected by the CALL and MALL. However, there was not a statistically significant difference between the CALL and MALL groups concerning motivation, foreign language learning anxiety, and self-efficacy. In light of the findings, a range of implications is suggested for relevant stakeholders.